THE INFLUENCE OF E-WOM AND PERCEIVED BENEFITS ON THE DECISION TO USE E-WALLET WITH CUSTOMER TRUST AS AN INTERVENING VARIABLE IN FEB UNSRAT STUDENT - Wuwungan, Angelika Regina; Tielung, Maria V.J.; Pandowo, Merinda H.C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This research investigates the influence of Electronic Word of Mouth (E-WOM) and perceived benefits on the decision to use e-wallets, with customer trust as an intervening variable, among students at the Faculty of Economics and Business (FEB) Sam Ratulangi University (UNSRAT). This study utilizes a quantitative research method, with 100 FEB UNSRAT students who are active e-wallet users as the sample. Data were collected through questionnaires and analyzed using the Smart PLS 4 program to test the hypotheses. The findings reveal that E-WOM positively affects customer trust but does not significantly influence the decision to use e-wallets. Conversely, perceived benefits positively and significantly influence both customer trust and the decision to use e-wallets. However, customer trust was not found to directly impact the decision to use e-wallets. The results suggest that while E-WOM builds trust, perceived benefits play a more significant role in determining e-wallet adoption. These findings highlight the importance of emphasizing the practical advantages of e-wallets to encourage wider usage among students.   Keywords: E-WOM, Perceived Benefits, Decision to Use, Customer Trust, E-Wallet